Model-based cost-minimization analysis of electrochemical hydrogen peroxide screening for oxidative stress evaluation using airways epithelial cell systems - Daniele Donzì; Maria Rita Marabeti; Paola Pinto; Anna Bonomolo; Serena Di Vincenzo; Maria Ferraro; Caterina Cascio; Giuseppina Chiappara; Chiara Cipollina; Nadia Moukri; Bernardo Patella; Andreina Bruno; et al. (In vitro models, 2026)
Oxidative stress is a common event in a variety of chronic diseases and its detection is confined to equipped laboratories with dedicated instruments and with personnel with high specialization. Electrochemical sensors have been demonstrated to be effective, easy-to-use, and reliable tools for quantifying extracellular hydrogen peroxide (H₂O₂) in airway epithelial preclinical models. Economic analyses of biomedical studies are increasingly needed. The present cost-minimization analysis compares the experimental costs of a traditional oxidative stress workflow with those of a screening strategy based on electrochemical H₂O₂ detection. The experimental design included bronchial epithelial cells exposed to cigarette smoke extract (CSE), as oxidative stress inducer, at three different concentrations and for three time points. As downstream events to CSE exposure, it was planned to assess mitochondrial superoxide production, toll-like receptor 4 (TLR4) and NF-kB expression, IL-8 gene expression and concentrations, and fluorescent advanced glycation end products (fAGE). The detection of H₂O₂ by electrochemical sensors in culture supernatants enables downstream events to be assessed only under conditions in which an extracellular oxidative response is detected, allowing the identification of the optimal time point and stimulus concentration. Considering a failure rate of 23% for both methods, the sensor-based approach reduces the overall experimental cost by 85.67% compared with the traditional ones. This value reflects the decrease in consumables and personnel time associated with preliminary screening performed with electrochemical sensors. In conclusion, the present analysis supports the utility of electrochemical sensors in optimizing research costs of preclinical studies aimed at assessing oxidative homeostasis perturbation and relative downstream events.

Discerning pristine and aged true-to-life microplastics through polarization-resolved digital holography and machine learning - Maria Pia Pierro; Marika Valentino; Serena Ducoli; Lisa Miccio; Vittorio Bianco; Stefania Federici; Pietro Ferraro (Journal of Environmental Chemical Engineering, 2026)

Structural constraints and environmental convergence: multilevel governance and $${CO}_{2}$$reduction in Italian provinces - Massimiliano Agovino; Maria D’Avino; Aniello Ferraro; Katia Marchesano (International Environmental Agreements: Politics, Law and Economics, 2026)

Tumor growth inhibitory activity of the P2X7 receptor antagonist AZ10606120 in two cell lines of human glioblastoma - Michela Graziano; Silvia Bono; Michela Pizzoferrato; Chiara Ferraro; Flavia Grossi; Pierluigi Navarra; Maria Martire; Lucia Lisi (Purinergic Signalling, 2026)
Glioblastoma multiforme (GBM) is among the most aggressive and lethal primary brain tumors. P2X7 is a purinergic receptor overexpressed in GBM, whose activation can promote tumor growth. Two major splice variants of the P2X7 receptor, isoforms A and B, are expressed in GBM cells. In our study, both isoforms A and B were present in GBM cells, with a slight prevalence of isoform B expression in the U87MG cell line compared to the T98G cell line. In GBM cell cultures, we evaluated the effects of P2X7 receptor activation/inhibition on cell growth. Exposure of GBM cells to various concentrations of ATP did not alter cellular activity, whereas inhibition of the P2X7 receptor with the antagonist AZ10606120, but not with A740003, significantly reduced GBM cell viability and proliferation. The U87MG cell line, which expresses the B isoform more highly, was more sensitive to the antiproliferative effects of AZ10606120. To clarify the mechanisms of AZ10606120-induced tumor inhibition, we measured the expression of proteins involved in cell repair and survival processes. AZ10606120 induced an increase in caspase-3 and p21 expression, demonstrating that P2X7R blockade can induce tumor cell death, likely by apoptosis. AZ10606120 also stimulated interleukin-6 (IL-6) release in GBM cells and induced phosphorylation of CREB and STAT3. Blockade of P2X7R by AZ10606120 appears to activate a pro-tumor IL-6/STAT3 axis. Increased IL-6 secretion and activation of the CREB and STAT3 pathways are negative prognostic signs that highlight the need to combine P2X7R inhibition with AZ10606120 with other therapies.

Increased TSLP and oxidative stress reflect airway epithelium injury upon cigarette smoke exposure. Is there a role for carbocysteine? - Paola Pinto; Daniele Donzì; Serena Di Vincenzo; Maria Ferraro; Valentina Lazzara; Maria Giuseppina Bruno; Nadia Moukri; Bernardo Patella; Rosalinda Inguanta; Elisabetta Pace (Toxicology, 2025)

Modeling movement patterns to identify thresholds of functional connectivity in fragmented forest landscapes - Michaela C. Peterson; Jennifer Bradham; Kristy Ferraro; Max Guillet; Alexine Keuroghlian; Milton Ribeiro; Maria Luisa S.P. Jorge (Biological Conservation, 2025)

Evaluation of Trends in Influenza A and B Viruses in Wastewater and Human Surveillance Data: Insights from the 2022–2023 Season in Italy - P. Mancini; D. Brandtner; C. Veneri; G. Bonanno Ferraro; M. Iaconelli; S. Puzelli; M. Facchini; G. Di Mario; P. Stefanelli; L. Lucentini; A. Muratore; Paolo Torlontano; et al. (Food and Environmental Virology, 2025)

Achieving nZEB goal through prefabricated buildings: Case study in Italy - Giovanni Miracco; Francesco Nicoletti; Vittorio Ferraro; Maurizio Muzzupappa; Vincenzo Maria Mattanò; Francesco Alberti (Energy and Buildings, 2025)

Tracking the Spread of the BA.2.86 Lineage in Italy Through Wastewater Analysis - C. Veneri; D. Brandtner; P. Mancini; G. Bonanno Ferraro; M. Iaconelli; E. Suffredini; M. Petrillo; G. Leoni; V. Paracchini; B. M. Gawlik; A. Marchini; Paolo Torlontano; et al. (Food and Environmental Virology, 2024)
The emergence of new SARS-CoV-2 variants poses challenges to global surveillance efforts, necessitating swift actions in their detection, evaluation, and management. Among the most recent variants, Omicron BA.2.86 and its sub-lineages have gained attention due to their potential immune evasion properties. This study describes the development of a digital PCR assay for the rapid detection of BA.2.86 and its descendant lineages, in wastewater samples. By using this assay, we analyzed wastewater samples collected in Italy from September 2023 to January 2024. Our analysis revealed the presence of BA.2.86 lineages already in October 2023 with a minimal detection rate of 2% which then rapidly increased, becoming dominant by January 2024, accounting for a prevalence of 62%. The findings emphasize the significance of wastewater-based surveillance in tracking emerging variants and underscore the efficacy of targeted digital PCR assays for environmental monitoring.

The combined use of biological investigations, bio chromatographic and in silico methods to solve the puzzle of badge and its derivative's toxicity - Ilaria Neri; Marialuisa Piccolo; Giacomo Russo; Maria Grazia Ferraro; Vincenzo Marotta; Rita Santamaria; Lucia Grumetto (Chemosphere, 2024)

Characterisation of microbial communities and quantification of antibiotic resistance genes in Italian wastewater treatment plants using 16S rRNA sequencing and digital PCR - Giusy Bonanno Ferraro; Carmelo Bonomo; David Brandtner; Pamela Mancini; Carolina Veneri; Rossella Briancesco; Anna Maria Coccia; Luca Lucentini; Elisabetta Suffredini; Dafne Bongiorno; Nicolò Musso; Stefania Stefani; et al. (Science of The Total Environment, 2024)

Tyndallized bacteria prime bronchial epithelial cells to mount an effective innate immune response against infections - Serena Di Vincenzo; Caterina Di Sano; Claudia D’Anna; Maria Ferraro; Velia Malizia; Andreina Bruno; Marta Cristaldi; Chiara Cipollina; Valentina Lazzara; Paola Pinto; Stefania La Grutta; Elisabetta Pace (Human Cell, 2024)
Airway epithelium represents a physical barrier against toxic substances and pathogens but also presents pattern recognition receptors on the epithelial cells that detect pathogens leading to molecule release and sending signals that activate both the innate and adaptive immune responses. Thus, impaired airway epithelial function and poor integrity may increase the recurrence of infections. Probiotic use in respiratory diseases as adjuvant of traditional therapy is increasingly widespread. There is growing interest in the use of non-viable heat-killed bacteria, such as tyndallized bacteria (TB), due to safety concerns and to their immunomodulatory properties. This study explores in vitro the effects of a TB blend on the immune activation of airway epithelium. 16HBE bronchial epithelial cells were exposed to different concentrations of TB. Cell viability, TB internalization, TLR2 expression, IL-6, IL-8 and TGF-βl expression/release, E-cadherin expression and wound healing were assessed. We found that TB were tolerated, internalized, increased TLR2, E-cadherin expression, IL-6 release and wound healing but decreased both IL-8 and TGF-βl release. In conclusion, TB activate TLR2 pathway without inducing a relevant pro-inflammatory response and improve barrier function, leading to the concept that TB preserve epithelial homeostasis and could be used as strategy to prevent and to manage respiratory infection, exacerbations included.

Wastewater-based Epidemiology and SARS-CoV-2: Variant Trends in the Apulia Region (Southern Italy) and Effect of Some Environmental Parameters - Francesco Triggiano; Osvalda De Giglio; Francesca Apollonio; Silvia Brigida; Fabrizio Fasano; Pamela Mancini; Giusy Bonanno Ferraro; Carolina Veneri; Giuseppina La Rosa; Elisabetta Suffredini; Luca Lucentini; Nicola Ungaro; et al. (Food and Environmental Virology, 2023)
During the COVID-19 pandemic, wastewater monitoring has been used to monitor the levels of SARS-CoV-2 RNA entering the sewerage system. In Italy, the Istituto Superiore di Sanità coordinated the SARI project (Sorveglianza Ambientale Reflue in Italia) to detect SARS-CoV-2 and its variants. In this study, the concentration of SARS-CoV-2 and its variants in raw wastewater against COVID-19 cases was evaluated together with the effect of temperature and precipitation on virus spread. We validated a predictive model, proposed by De Giglio et al., 2021, to establish the number of COVID-19 cases/100,000 inhabitants. A receiver operating characteristic curve model was applied to predict the number of COVID-19 cases and Poisson regression was applied to study the effect of temperature and rainfall on viral load. In Apulia, from October 2021 to December 2022, we analyzed 1041 samples, of which 985 (94.6%) tested positive for SARS-CoV-2. Median atmospheric temperature was inversely proportional to viral load in wastewater; no correlation was found with precipitation. The predictive model confirmed that at least 11 cases/100,000 inhabitants would occur in the 15 days following the detection of the virus in wastewater. Environmental surveillance of SARS-CoV-2 can be used to map the virus and its variants.

Evaluation of concentration procedures, sample pre-treatment, and storage condition for the detection of SARS-CoV-2 in wastewater - Francesca Cutrupi; Michele Rossi; Maria Cadonna; Elisa Poznanski; Serena Manara; Mattia Postinghel; Giulia Palumbi; Marta Bellisomi; Elena Nicosia; Giorgia Allaria; Lorenzo Dondero; Carolina Veneri; et al. (Environmental Science and Pollution Research, 2023)
Crucial information on the pandemic’s spread has been gathered by monitoring the trend of SARS-CoV-2 in wastewater. This surveillance has highlighted that the initial concentration is a critical step of the analytical procedure due to the low viral titer that may be present in this matrix. This paper presents the results of the evaluation of two different wastewater concentration protocols to determine the most efficient and cost-effective. The two methods tested were the following: (a) a biphasic separation system with PEG-dextran and (b) a PEG/NaCl precipitation protocol. Other aspects of the detection method were also investigated including the influence of storage temperature on virus recovery and the heat treatment of pasteurization, which aims to make samples safer for operators and the environment. The PEG/NaCl precipitation method was found to perform better than the biphasic separation system, allowing for more sensitive identification of the presence of the virus and the detection of a higher viral titer than that identified with the biphasic separation in all results. Storage of the samples at 4.3±0.2°C for up to 3 weeks did not adversely affect the virus titer and the pasteurization pre-treatment increases operator safety and maintains the identification of the viral concentration. Graphical abstract

Wastewater surveillance of SARS-CoV-2 variants in October–November 2022 in Italy: detection of XBB.1, BA.2.75 and rapid spread of the BQ.1 lineage - G. La Rosa; D. Brandtner; G. Bonanno Ferraro; C. Veneri; P. Mancini; M. Iaconelli; L. Lucentini; C. Del Giudice; L. Orlandi; Achille Palma; Adelaide Calabria; Agnese Carnevali; et al. (Science of The Total Environment, 2023)

Lipophilicity profiling and cell viability assessment of a selected panel of endocrine disruptors - Giacomo Russo; Marialuisa Piccolo; Ilaria Neri; Maria Grazia Ferraro; Rita Santamaria; Lucia Grumetto (Chemosphere, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Multivariate tools to investigate the spatial contaminant distribution in a highly anthropized area (Gulf of Naples, Italy) - Matilda Mali; Antonella Di Leo; Santina Giandomenico; Lucia Spada; Nicola Cardellicchio; Maria Calò; Alessandra Fedele; Luciana Ferraro; Alfonsa Milia; Monia Renzi; Francesca Massara; Tommaso Granata; et al. (Environmental Science and Pollution Research, 2022)
The Gulf of Naples located in a high anthropized coastal area is subjected to an infrastructural intervention for the installation of a submarine power pipeline. In order to evaluate the distribution of contaminants in the seafloor sediments, a preliminary study has been conducted in the area using multivariate techniques. The statistic approach was performed to gain insights on the occurrence of organic and inorganic contaminants within the area, aiming to identify the relevant hot spots. Three geographical sub-areas influenced by different contaminant association were recognized: Torre Annunziata (TA), Capri (CA), and middle offshore (MO). TA and CA resulted marked by a severe contamination pattern due to anthropogenic pressures. In addition, the influence of the depositional basin in governing the contamination trend has been pointed out. The supervised technique PLS_DA resulted to be a powerful tool in addressing the complexity of the huge dataset acquired during the marine survey, highlighting the main trends in the variability of quality indicators, orienting thus the deeper investigations during follow-up monitoring activities.

Mycochemicals in wild and cultivated mushrooms: nutrition and health - Francesca Cateni; Maria Letizia Gargano; Giuseppe Procida; Giuseppe Venturella; Fortunato Cirlincione; Valeria Ferraro (Phytochemistry Reviews, 2022)
The mushrooms have contributed to the development of active ingredients of fundamental importance in the field of pharmaceutical chemistry as well as of important tools in human and animal health, nutrition, and functional food. This review considers studies on the beneficial effects of medicinal mushrooms on the nutrition and health of humans and farm animals. An overview of the chemical structure and composition of mycochemicals is presented in this review with particular reference to phenolic compounds, triterpenoids and sterols, fatty acids and lipids, polysaccharides, proteins, peptides, and lectins. The nutritional value and chemical composition of wild and cultivated mushrooms in Italy is also the subject of this review which also deals with mushrooms as nutraceuticals and the use of mushrooms in functional foods. The nutraceutical benefits of UV irradiation of cultivated species of basidiomycetes to generate high amounts of vitamin D2 is also highlighted and the ability of the muhsrooms to inhibit glycation is analyzed. Finally, attention is paid to studies on bioactivities of some Italian wild and cultivated mushrooms with particular reference to species belonging to the genus Pleurotus . The review highlights the potential of medicinal mushrooms in the production of mycochemicals that represent a source of drugs, nutraceutical, and functional food. Graphic abstract

Spinocerebellar Ataxia Type 1: One-Year Longitudinal Study to Identify Clinical and MRI Measures of Disease Progression in Patients and Presymptomatic Carriers - Anna Nigri; Lidia Sarro; Alessia Mongelli; Anna Castaldo; Luca Porcu; Chiara Pinardi; Marina Grisoli; Stefania Ferraro; Laura Canafoglia; Elisa Visani; Maria Grazia Bruzzone; Lorenzo Nanetti; et al. (The Cerebellum, 2022)

Cultivated mushrooms: importance of a multipurpose crop, with special focus on Italian fungiculture - Valeria Ferraro; Giuseppe Venturella; Lorenzo Pecoraro; Wenyuan Gao; Maria Letizia Gargano (Plant Biosystems, 2022)

Is Battarrea phalloides really an endangered species? - Maria Letizia Gargano; Giuseppe Venturella; Valeria Ferraro (Plant Biosystems, 2021)

Duplex high resolution melting analysis (dHRMA) to detect two hot spot CYP24A1 pathogenic variants (PVs) associated to idiopathic infantile hypercalcemia (IIH) - Maria De Bonis; Elisa De Paolis; Maria Elisabetta Onori; Giorgia Mazzuccato; Antonio Gatto; Pietro Ferrara; Pietro Manuel Ferraro; Andrea Urbani; Angelo Minucci (Molecular Biology Reports, 2021)
Pathogenic variants (PVs) in CYP24A1 gene are associated with Idiopathic Infantile Hypercalcemia disease (IIH). The identification of CYP24A1 PVs can be a useful tool for the improvement of target therapeutic strategies. Aim of this study is to set up a rapid and inexpensive High Resolution Melting Analysis (HRMA)-based method for the simultaneous genotyping of two hot spot PVs in CYP24A1 gene, involved in IIH. A duplex-HRMA (dHRMA) was designed in order to detect simultaneously CYP24A1 c.428_430delAAG , p.(Glu143del) (rs777676129) and c.1186C > T , p.(Arg396Trp) (rs114368325), in peculiar cases addressed to our Laboratory. dHRMA was able to identify clearly and simultaneously both hot spot CYP24A1 PVs evaluating melting curve shape and melting temperature (T m ). This is the first dHRMA approach to rapidly screen the two most frequent CYP24A1 PVs in peculiar case, providing useful information for diagnosis and patient management in IIH disease.

Automatic multispectral MRI segmentation of human hippocampal subfields: an evaluation of multicentric test–retest reproducibility - Andrea Chiappiniello; Roberto Tarducci; Cristina Muscio; Maria Grazia Bruzzone; Marco Bozzali; Pietro Tiraboschi; Anna Nigri; Claudia Ambrosi; Elena Chipi; Stefania Ferraro; Cristina Festari; Roberto Gasparotti; et al. (Brain Structure and Function, 2021)
Accurate and reproducible automated segmentation of human hippocampal subfields is of interest to study their roles in cognitive functions and disease processes. Multispectral structural MRI methods have been proposed to improve automated hippocampal subfield segmentation accuracy, but the reproducibility in a multicentric setting is, to date, not well characterized. Here, we assessed test–retest reproducibility of FreeSurfer 6.0 hippocampal subfield segmentations using multispectral MRI analysis pipelines (22 healthy subjects scanned twice, a week apart, at four 3T MRI sites). The harmonized MRI protocol included two 3D-T1, a 3D-FLAIR, and a high-resolution 2D-T2. After within-session T1 averaging, subfield volumes were segmented using three pipelines with different multispectral data: two longitudinal (“long_T1s” and “long_T1s_FLAIR”) and one cross-sectional (“long_T1s_FLAIR_crossT2”). Volume reproducibility was quantified in magnitude (reproducibility error—RE) and space (DICE coefficient). RE was lower in all hippocampal subfields, except for hippocampal fissure, using the longitudinal pipelines compared to long_T1s_FLAIR_crossT2 (average RE reduction of 0.4–3.6%). Similarly, the longitudinal pipelines showed a higher spatial reproducibility (1.1–7.8% of DICE improvement) in all hippocampal structures compared to long_T1s_FLAIR_crossT2. Moreover, long_T1s_FLAIR provided a small but significant RE improvement in comparison to long_T1s ( p = 0.015), whereas no significant DICE differences were found. In addition, structures with volumes larger than 200 mm 3 had better RE (1–2%) and DICE (0.7–0.95) than smaller structures. In summary, our study suggests that the most reproducible hippocampal subfield FreeSurfer segmentations are derived from a longitudinal pipeline using 3D-T1s and 3D-FLAIR. Adapting a longitudinal pipeline to include high-resolution 2D-T2 may lead to further improvements.

Astrocytic Mechanisms Involving Kynurenic Acid Control Δ9-Tetrahydrocannabinol-Induced Increases in Glutamate Release in Brain Reward-Processing Areas - Maria E. Secci; Paola Mascia; Claudia Sagheddu; Sarah Beggiato; Miriam Melis; Andrea C. Borelli; Maria C. Tomasini; Leigh V. Panlilio; Charles W. Schindler; Gianluigi Tanda; Sergi Ferré; Charles W. Bradberry; et al. (Molecular Neurobiology, 2019)

The neural correlates of lexical processing in disorders of consciousness - Anna Nigri; Eleonora Catricalà; Stefania Ferraro; Maria Grazia Bruzzone; Ludovico D’Incerti; Davide Sattin; Davide Rossi Sebastiano; Silvana Franceschetti; Giorgio Marotta; Riccardo Benti; Matilde Leonardi; Stefano F. Cappa (Brain Imaging and Behavior, 2017)

Cerebrospinal fluid anti-Epstein-Barr virus specific oligoclonal IgM and IgG bands in patients with clinically isolated and Guillain-Barré syndrome - Diana Ferraro; Veronica Galli; Anna Maria Simone; Roberta Bedin; Francesca Vitetta; Elisa Merelli; Paolo Frigio Nichelli; Patrizia Sola (Journal of NeuroVirology, 2017)

MD2 expression is reduced in large airways of smokers and COPD smokers - Elisabetta Pace; Maria Ferraro; Giuseppina Chiappara; Patrizio Vitulo; Loredana Pipitone; Serena Di Vincenzo; Mark Gjomarkaj (Molecular and Cellular Biochemistry, 2015)

Structural evidences for a secondary gold binding site in the hydrophobic box of lysozyme - Giarita Ferraro; Lara Massai; Luigi Messori; Maria Agostina Cinellu; Antonello Merlino (BioMetals, 2015)

Fluticasone furoate maintains epithelial homeostasis via leptin/leptin receptor pathway in nasal cells - Andreina Bruno; Stefania Gerbino; Maria Ferraro; Liboria Siena; Angela Bonura; Paolo Colombo; Stefania La Grutta; Salvatore Gallina; Antonella Ballacchino; Marco Giammanco; Mark Gjomarkaj; Elisabetta Pace (Molecular and Cellular Biochemistry, 2014)

Evolution of the Sele River coastal plain (southern Italy) during the Late Quaternary by inland and offshore stratigraphical analyses - Pietro P. C. Aucelli; Vincenzo Amato; Francesca Budillon; Maria Rosaria Senatore; Sabrina Amodio; Carmine D’Amico; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Holocene environmental evolution of the costal sector in front of the Poseidonia-Paestum archaeological area (Sele plain, southern Italy) - Vincenzo Amato; Pietro Patrizio Ciro Aucelli; Bruno D’Argenio; Simone Da Prato; Luciana Ferraro; Gerardo Pappone; Paola Petrosino; Carmen Maria Rosskopf; Elda Russo Ermolli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2012)

Oberflächennahe Geothermie und ihre potenziellen Auswirkungen auf Grundwasserökosysteme - Heike Brielmann; Tillmann Lueders; Kathrin Schreglmann; Francesco Ferraro; Maria Avramov; Verena Hammerl; Philipp Blum; Peter Bayer; Christian Griebler (Grundwasser, 2011)

Genotoxic effects of produced waters in mosquito fish (Gambusia affinis) - Ilaria Caliani; Serena Porcelloni; Gabriele Mori; Giada Frenzilli; Maria Ferraro; Letizia Marsili; Silvia Casini; Maria Cristina Fossi (Ecotoxicology, 2009)

A model of visual perception - Laura Borello; Mario Ferraro; Piero Penengo; Maria Lia Rossotti (Biological Cybernetics, 1981)